Phyllanthusspp. Exerts Anti-Angiogenic and Anti-Metastatic Effects Through Inhibition on Matrix Metalloproteinase Enzymes - Tang, Yin-Quan; Jaganath, Indu Bala; Manikam, Rishya; Sekaran, Shamala Devi (Taylor & Francis, 2015)
Tumor angiogenesis and metastasis are the major causes for high morbidity and mortality rates in cancer patient. Modulation on tumor angiogenesis and metastasis provides opportunities to halt progression of cancer. From our previous findings, Phyllanthus plant possesses antiproliferative effects on melanoma and prostate cancer cell lines and induction of apoptosis. The main aims of the present work were further investigated on the antimetastatic and antiangiogenic effects on cancer cells (MeWo and PC-3) and human umbilical vein endothelial cells (HUVECs) of 4 Phyllanthus species (P.amarus, P.niruri, P.urinaria and P.watsonii). Phyllanthus extracts significantly inhibited cell adhesion, migration, invasion, and transendothelial migration activities of cancer (MeWo and PC-3) cells in a dose-dependent manner (P < 0.05) by cell-matrix adhesion, Transwell migration, invasion, and transendothelial migration assays. Phyllanthus extracts were exhibited low cytotoxicity on HUVECs up to a concentration of 500.0 g/ml by MTS reduction assay. Phyllanthus extracts also exhibited antiangiogenic effects through inhibition of migration, invasion, and microcapillary like-tube structure formation in HUVECs. These observations were due to alteration in activities of matrix metalloproteinase (MMP) -2, -7, -9, and -26 in treated-endothelial and cancer cells by zymographies. These findings suggest that Phyllanthus plant has the potential to inhibit tumour metastasis and angiogenesis through the suppression of MMP enzymes.